Enhancing drought tolerance in faba bean using ascorbic and humic acids: role of antioxidant enzymes and compatible solutes - Hussein S. Al-Demrdash; Anam Ayyoub; Omar E. A. ziton; Saber A.E. Mowafy; El-Sayed E. A. El-Sayed; Uthman Balgith Algopishi; Ahmed Ezzat Ahmed; Khaled A. El-Tarabily; Synan F. AbuQamar; Mohsin Mahmood; El-Sayed M. Desoky (BMC Plant Biology)
Abstract Drought is a major environmental stress, particularly in arid regions, where it severely limits faba bean productivity. Foliar-applied ascorbic acid (AsA) and soil-applied humic acid (HA) significantly improved drought tolerance in three faba bean cultivars by enhancing physiological performance and mitigating oxidative damage under moderate (300 mm) and severe (200 mm) drought conditions. Drought stress significantly reduced chlorophyll content (up to -57.5%), relative water content (RWC, -37.9%), and yield traits such as plant height (− 9.6%) and seed yield (− 20.8%), while increasing oxidative stress markers like malondialdehyde (MDA, + 192.8%) and hydrogen peroxide (H₂O₂, + 105.0%). AsA and HA alleviated these effects, improving chlorophyll retention (up to + 33.7%), water status (+ 17.0%), and reducing MDA(− 19.1%) and electrolyte leakage (− 11.5%). Enhanced accumulation of proline (+ 27.4%) and soluble sugars (+ 18.0%) contributed to improved osmotic balance, while antioxidant enzyme activities (superoxide dismutase, catalase, peroxidase, ascorbate peroxidase, and glutathione reductase) were also upregulated, particularly with AsA. These treatments improved growth, yield traits, and water use efficiency, especially under drought stress, with Nubaria-5 showing the highest drought resilience. This cultivar exhibited superior pigment stability, antioxidant activity, and yield preservation across stress conditions. Significant interactions among irrigation regime, biostimulant, and cultivar highlighted the importance of genotype-specific responses. Heatmap analysis confirmed the consistent effectiveness of AsA, particularly under severe drought in Nubaria-5. Overall, AsA and HA function as effective biostimulants for enhancing drought resilience in faba bean by improving photosynthetic efficiency, water relations, and antioxidative capacity, with AsA showing greater overall efficacy.